The Impact of Cash Holding on Debt Cost - Chaieb, Souad (International Journal of Economics and Financial Issues, 2021)
This paper seeks to highlight the potential relationship that could exist between cash holding and the cost of debt. It also tries to underline the effect of the control block moderator and of operating risk on this relationship. The study was conducted on a sample of 100 French companies listed in the SBF120 index over a five-year period. In general, the results are conclusive in all cases. However, the holding of cash has a negative and statistically significant effect. This result confirms the H1 hypothesis. In other words, the more liquidity the company retains, the lower the cost of debt. This relationship is confirmed by the arbitrage pricing theory according to which, above a certain threshold, the debt increases the risk of financial distress resulting from the direct costs associated with administrative and judicial orders in case of bankruptcy and indirect costs linked to a loss of credibility with the partners and especially with its creditors. To deal with this risk, firms are required to retain liquidity. Keywords: cost of debt, cash holding, control block, operating risk JEL Classification: G30 DOI: https://doi.org/10.32479/ijefi.11738